MANAJERIAL COMPETENCE OF MADRASAH PRINCIPALS IN BUILDING STAKEHOLDER COMMITMENT TO THE QUALITY OF MADRASAH ALIYAH IN RIAU PROVINCE - Sudur; Kasful Anwar Us; Kemas Imron Rosadi; Asrulla (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to examine the managerial competencies of madrasah principals, their commitment to fostering stakeholder commitment, and the collective commitment of both principals and stakeholders to the quality of Madrasah Aliyah. The usefulness of this research is to enrich the scientific paradigm in the field of Islamic Education Management, specifically in the study of Human Resource Management.This research is qualitative, employing interviews and observations as its methods. The research informants consist of madrasah principals and stakeholders, particularly educators and education staff at Madrasah Aliyah in Riau Province. Data collection techniques include interviews and observations, using data collection instruments as interview guidelines. The collected data is then analyzed.The findings of the study are as follows:(1) The planning conducted by the madrasah principal involves policy formulation through deliberations, discussions, and meetings with stakeholders, including vice principals, educators, education staff, and even parents, during the planning, implementation, and evaluation stages. Policies to enhance the competency and commitment of principals and educators are implemented through workshops, training sessions, and seminars.(2) The organization of work procedures by the madrasah principal includes direct coordination with teachers, delegation of duties to vice principals, clear job specifications, and structured task distribution based on the organizational hierarchy.(3) The management of stakeholder performance, particularly educators and education staff, focuses on self-competence, commitment, self-motivation, perseverance, humanity, economic factors, salaries, certifications, and effective leadership by the madrasah principal, including teacher development programs.(4) The supervision of stakeholder performance by the madrasah principal follows an open system monitoring model, which includes input, process, output, and outcome. The input refers to educators with at least a bachelor's or master's degree specializing in the required field of education. The process involves training, education, and supervision by the principal. The output is reflected in the quality of services provided to both internal and external stakeholders of the madrasah. The outcome is the achievement of organizational goals and the improvement of madrasah quality.Based on the research findings, it is concluded that the managerial competencies of madrasah principals enhance the commitment of Madrasah Aliyah stakeholders in Riau Province. Recommendations are proposed to the Provincial and District Education Offices to develop training programs for madrasah principals and stakeholders.